A Solid‐Phase Conversion Sulfur Cathode with Full Capacity Utilization and Superior Cycle Stability for Lithium‐Sulfur Batteries. Issue 10 (17th January 2022) - Wu, Xiangjiang; Zhang, Qian; Tang, Guo; Cao, Yuliang; Yang, Hanxi; Li, Hui; Ai, Xinping
Abstract: Solid phase conversion sulfur cathode is an effective strategy for eliminating soluble polysulfide intermediates (LiPSs) and improving cyclability of Li‐S batteries. However, realizing such a sulfur cathode with high sulfur loading and high capacity utilization is very challenging due to the insulating nature of sulfur. In this work, a strategy is proposed for fabricating solid phase conversion sulfur cathode by encapsulating sulfur in the mesoporous channels of CMK‐3 carbon to form a coaxially assembled sulfur/carbon (CA‐S/C) composite. Vinyl carbonate (VC) is simultaneously utilized as the electrolyte cosolvent to in‐situ form a dense solid electrolyte interface (SEI) on the CA‐S/C composite surface through its nucleophilic reaction with the freshly generated polysulfides at the beginning of initial discharge, thus separating the direct contact of interior sulfur with the outer electrolyte. As expected, such a CA‐S/C cathode can operate in a solid phase conversion manner in the VC‐ether cosolvent electrolyte to exhibit a full capacity utilization (1667 mA h g –1, ≈100%), a high rate capability of 2.0 A g –1 and excellent long‐term cyclability over 500 cycles even at a high sulfur loading (75%, based on the weight of CA‐S/C composite), demonstrating great promise for constructing high‐energy‐density and cycle‐stable Li‐S batteries. Abstract : A solid‐phase conversion sulfur cathode with full capacity utilization and superior cycling performance in VC‐ether cosolvent electrolyte is successfully developed by encapsulating sulfur in the mesoporous channels of CMK‐3 carbon to form a coaxially assembled sulfur/carbon (CA‐S/C) composite. This composite exhibits an ultrahigh reversible capacity of 1667 mA h g −1 and an extremely stable cyclability over 500 cycles.